Study of Flexor Carpi Ulnaris (FCU) Muscle Strength in Dominant and Non-Dominant Hands in Various Hand Postures - S., Krishnakumar; M.C. , Jobin Christ; K. , Vighnesh; K. , Vellaisamy; M. , Suriya Prakash; T. , Pavin Kumar; P. , Prasanth; M. , Saktheeshwar (International Journal of Psychosocial Rehabilitation, 2020)
The human hand is a versatile organ that adapts to various environments in day-to-day life. Hand muscles provide stability to the joints to deal with objects of various sizes and shapes in position. The main aim of this research is to identify the posture and the hand (dominant/non-dominant) that extracts maximum effort from the FCU muscle. Further, it was hypothesized that if a particular posture demands a comparatively greater effort from the muscle, it will drive the participants to hold it for a longer period of time compared to the other postures. Flexor Carpi Ulnaris (FCU) muscle strength was determined by subjecting the wrists of both dominant and non-dominant hands (DH and NDH) to prolonged flexion and extension. The maximum duration sustained by the participants for each posture is the direct measure of the FCU muscle strength in terms of amplitude (voltage) and time (milliseconds). The postures were: tight fist; tight fist combined with wrist flexion; and palm stretch combined with wrist flexion. The effort exerted by the FCU muscle varied individually for all the postures. The outcomes showed that the tight fist combined with wrist flexion posture was tougher compared to the remaining postures since the participants felt it difficult to hold the posture for a longer period of time.